Cognitive Engagement during Emergency Remote Teaching: How Students Struggle - Audi Yundayani; Fiki Alghadari (Universitas Pelita Harapan, 2023)
AbstractThe COVID-19 pandemic situation has had an impact on the higher education system in Indonesia. It created an online learning ecosystem to enact the essential role of cognitive engagement by students. This qualitative research utilized multimodal data collection to examine students' voices to assess how they perceived the cognitive engagement dimension during emergency remote teaching (ERT). Data were gathered from 60 students from three higher education institutions in Indonesia's urban areas. The findings revealed that the ERT environment requires students to self-regulate their learning by employing their preferred strategies to comprehend the material. Moreover, they engage in meaningful learning by relating content to their prior experiences and knowledge. Students also believe that teachers play a vital role in ERT as authoritative figures and focal learning points. They view teachers as the main agents for fostering and enhancing their cognitive engagement. This study draws attention to the need for continuous teacher professional development in ERT by concentrating on students' needs. Bahasa Indonesia Abstrak: Situasi pandemi COVID-19 berdampak pada sistem pendidikan tinggi di Indonesia. Ini menciptakan ekosistem pembelajaran online untuk memberlakukan peran penting keterlibatan kognitif oleh siswa. Penelitian kualitatif ini menggunakan pengumpulan data multimodal untuk memeriksa suara siswa untuk menilai bagaimana mereka merasakan dimensi keterlibatan kognitif dalam fenomena pengajaran jarak jauh darurat. Data dari 60 mahasiswa dari tiga perguruan tinggi yang berada di perkotaan Indonesia. Hasil penelitian menunjukkan bahwa pengaturan pengajaran darurat mengharuskan siswa untuk menerapkan proses belajar mandiri dengan mengatur preferensi metode pembelajaran mereka untuk memahami isi materi. Bahkan, mereka melakukan pembelajaran yang bermakna dengan menghubungkan konten dengan pengalaman dan pengetahuan mereka sebelumnya. Mereka juga percaya bahwa guru, serta siswa, memainkan peran penting dalam lingkungan pengajaran darurat. Selain itu, karena keyakinan mereka bahwa guru masih menjadi pusat pembelajaran sebagai sosok otoriter, mereka menggambarkan guru sebagai agen utama untuk mempromosikan dan meningkatkan keterlibatan kognitif mereka. Studi ini lebih menarik perhatian pada perlunya pengembangan profesional guru yang berkelanjutan dalam situasi pengajaran darurat dengan berkonsentrasi pada kebutuhan siswa.